Pedagogical Strategies employed by Literature and Linguistic teachers: A case study in Banke, Nepal (Conocimiento Educativo, 2024)
This study aimed to investigate the techniques employed by Literature and Linguistic English teachers in teaching grammar to 11th-grade students and to compare their teaching strategies. The research design adopted a qualitative method, collecting data from four randomly selected public and private schools in the Banke district. Observation checklists and diary writing for classroom observations served as the primary tools for data collection. Thematic analysis was applied to interpret the gathered data. The results revealed that literature and linguistic teachers predominantly utilized similar techniques. However, linguistic teachers did not employ expected grammar teaching techniques, suggesting that pedagogical competence in grammar has limited utility. Instead, teachers tended to rely on methods that facilitated their teaching process. The study’s findings imply a necessity for additional professional development for English language teachers, particularly in the domain of grammar teaching pedagogy. Furthermore, these results could inform curriculum development and teacher training programs, aiming to enhance grammar instruction and ultimately improve students’ language proficiency.
Keywords: Literature; Linguistic; Grammar; Pedagogy; Professional development